Evaluation of Oxidative Stress and LeptinLevel in Samples of Iraqi Obese Women - Ali, Israa M. Mubarak; Yenzeel, Jabbar H.; Al-ansari, Hani M. Saleh (Iraqi Journal of Science, 2020)
The aim of this study is to investigate oxidative stress and leptinlevel in obese women. Fifty obese women with BMI value of ≥ 30.0 kg/m2 and thirty healthy women with BMI<24.9 kg/m2 were involved in the study during their attendance at Gastroenterology and Liver Hospital/ Medical city in Baghdad province from October 2018 to February 2019. The age range for all women was 30-50 years. Blood samples were collected from each participant for the evaluation of the levels of leptin hormone, Super Oxide Dismutase (SOD), and Malondialdehyde (MDA). The results of BMI, leptin hormone, MDA and SOD showed highly significant increase (P<0.01) in obese women in comparison with the control group.Results: The results show that BMI value were significantly higher (P<0.01) in obese women (41.90 ± 0.87kg/m2) in comparison with the control (23.58 ± 0.28kg/m2). The level of leptin hormone was significantly higher(P<0.01) in obese women (1444.00 ± 10.67pg/ml) in comparison with the control (932.26 ± 25.92pg/ml). Also, MDA level was significantly higher(P<0.01) in obese women (6.81 ± 0.29mg/dl) in comparison with the control (4.53 ± 0.44) mg/dl. The level of SOD was significantly higher(P<0.01) in obese women (15.67 ± 1.42mg/dl) in comparison with the control group (3.75 ± 0.60mg/dl).Conclusions: Obesity is detected by the level of leptin Hormone; leptin is regarded as a good parameter for monitoring obesity,showing a high increasewith increasing BMI.Theincrease in obesity causes oxidant stress and formation of MDA that is considered as a major risk factor in obesity,where adecrease in antioxidants was also recorded.